Answer:
The derivative of the function does not exist.
Step-by-step explanation:
The alternative form of a derivative is given by:
![f'(c)= \lim_{x \to c} \dfrac{f(x)-f(c)}{x-c}](https://tex.z-dn.net/?f=f%27%28c%29%3D%20%5Clim_%7Bx%20%5Cto%20c%7D%20%5Cdfrac%7Bf%28x%29-f%28c%29%7D%7Bx-c%7D)
Our function is defined as:
h(x)=|x+8|
i.e. h(x)= -(x+8) when x+8<0
and x+8 when x+8≥0
i.e. h(x)= -x-8 when x<-8
and x+8 when x≥-8
Hence now we find the derivative of the function at c=-8
i.e. we need to find the Left hand derivative (L.H.D.) and Right hand derivative (R.H.D) of the function.
The L.H.D at a point 'a' is calculated as:
![\lim_{x \to a^-} \dfrac{f(x)-f(a)}{x-a}\\\\=\lim_{h \to0} \dfrac{f(a-h)-f(a)}{a-h-a}= \lim_{h\to 0} \dfrac{f(a-h)-f(a)}{-h}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20a%5E-%7D%20%5Cdfrac%7Bf%28x%29-f%28a%29%7D%7Bx-a%7D%5C%5C%5C%5C%3D%5Clim_%7Bh%20%5Cto0%7D%20%5Cdfrac%7Bf%28a-h%29-f%28a%29%7D%7Ba-h-a%7D%3D%20%5Clim_%7Bh%5Cto%200%7D%20%20%5Cdfrac%7Bf%28a-h%29-f%28a%29%7D%7B-h%7D)
Similarly R.H.D is given by:
![\lim_{x \to a^+} \dfrac{f(x)-f(a)}{x+a}\\\\=\lim_{h \to 0} \dfrac{f(a+h)-f(a)}{a+h-a}= \lim_{h\to 0} \dfrac{f(a+h)-f(a)}{h}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20a%5E%2B%7D%20%5Cdfrac%7Bf%28x%29-f%28a%29%7D%7Bx%2Ba%7D%5C%5C%5C%5C%3D%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7Bf%28a%2Bh%29-f%28a%29%7D%7Ba%2Bh-a%7D%3D%20%5Clim_%7Bh%5Cto%200%7D%20%5Cdfrac%7Bf%28a%2Bh%29-f%28a%29%7D%7Bh%7D)
Now for L.H.D we have to use the function h(x) =-x-8
and for R.H.D. we have to use the function h(x)=x+8
L.H.D.
we have a=-8
![\lim_{x \to (-8)^-} \dfrac{h(x)-h(-8)}{x-(-8)}\\\\= \lim_{h \to0} \dfrac{h(-8-h)-h(-8)}{-8-h-(-8)}= \lim_{h\to 0} \dfrac{h(-8-h)-h(-8)}{-h}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20%28-8%29%5E-%7D%20%5Cdfrac%7Bh%28x%29-h%28-8%29%7D%7Bx-%28-8%29%7D%5C%5C%5C%5C%3D%20%5Clim_%7Bh%20%5Cto0%7D%20%5Cdfrac%7Bh%28-8-h%29-h%28-8%29%7D%7B-8-h-%28-8%29%7D%3D%20%5Clim_%7Bh%5Cto%200%7D%20%5Cdfrac%7Bh%28-8-h%29-h%28-8%29%7D%7B-h%7D)
= ![\lim_{h \to 0} \dfrac{8+h-8-0}{-h}= \lim_{h \to 0}\dfrac{h}{-h}=-1](https://tex.z-dn.net/?f=%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B8%2Bh-8-0%7D%7B-h%7D%3D%20%5Clim_%7Bh%20%5Cto%200%7D%5Cdfrac%7Bh%7D%7B-h%7D%3D-1)
similarly for R.H.D.
![\lim_{x \to (-8)^+} \dfrac{h(x)-h(-8)}{x-(-8)}\\\\=\lim_{h \to 0} \dfrac{h(-8+h)-h(-8)}{-8+h-(-8)}= \lim_{h\to 0} \dfrac{h(-8+h)-h(-8)}{h}](https://tex.z-dn.net/?f=%5Clim_%7Bx%20%5Cto%20%28-8%29%5E%2B%7D%20%5Cdfrac%7Bh%28x%29-h%28-8%29%7D%7Bx-%28-8%29%7D%5C%5C%5C%5C%3D%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7Bh%28-8%2Bh%29-h%28-8%29%7D%7B-8%2Bh-%28-8%29%7D%3D%20%5Clim_%7Bh%5Cto%200%7D%20%5Cdfrac%7Bh%28-8%2Bh%29-h%28-8%29%7D%7Bh%7D)
![\lim_{h \to 0} \dfrac{-8+h+8-0}{h}=\lim_{h \to 0}\dfrac{h}{h}=1](https://tex.z-dn.net/?f=%5Clim_%7Bh%20%5Cto%200%7D%20%5Cdfrac%7B-8%2Bh%2B8-0%7D%7Bh%7D%3D%5Clim_%7Bh%20%5Cto%200%7D%5Cdfrac%7Bh%7D%7Bh%7D%3D1)
Now as L.H.D≠R.H.D.
Hence, the function is not differentiable.
Answer:
Step-by-step explanation:
From the given question.
We can write the null hypothesis & the alternative hypothesis as:
Null hypothesis:
![\mathbf{H_o: \mu \leq 6}](https://tex.z-dn.net/?f=%5Cmathbf%7BH_o%3A%20%5Cmu%20%5Cleq%206%7D)
Alternative hypothesis:
![\mathbf{H_{a}:\mu >6}](https://tex.z-dn.net/?f=%5Cmathbf%7BH_%7Ba%7D%3A%5Cmu%20%3E6%7D)
From above, let's think about the type I error we could make and the type II error we could make.
<u>Type I error:</u>
The type I error at the null hypothesis showcases that the snow level is at 6 inches or below 6 inches, but we falsely concluded that the snow level is high above sea level.
<u>Type II error:</u>
Here, the snow level is literally above 6 inches, hence, we failed to conclude that the snow level is above 6 inches.
Thus, the consequences of the above analysis showcase that type II error has higher severe consequences because it may result in a situation that may endanger the passengers' safety.
Answer:
-3
Step-by-step explanation:
Answer:
The worker can get a piece of the diamonds using 48÷8 which it is 6.
Step-by-step explanation:
I hope that it is what you're looking for. I hope this helps
Answer:
40 inch
Step-by-step explanation:
1 inch=2.54cm
so 40 inch= 101.6 cm